From history of ukrainian diaspora in the Republic of Kazakhstan (International relations and international law Journal, 2018)
Under the conditions of intensification of migration processes, reinforcement of consolidation ofimmigrant groups, the expansion of democracy and multiculturalism policies, the ethnic lobbyism hasbecome one of the most significant power leverage both in the economy and policy of many countries.The practice of using the political potential of Diasporas for the development of their Motherland and itsinternational relations has increased.Diaspora is the settling of a significant part of the people outside their country or ethnic territory.The main reason for the formation of a diaspora is migration beyond the homeland due to economic,political, religious or other reasons. In it are the essence, rationale and critical importance of knowledgeof a diaspora in any country, including its migratory movements.The Ukrainian diaspora has significant potential to strengthen Ukraine’s position in the internationalarena, to lobby the declared foreign policy interests in the countries of residence and international organizations,to promote the improvement of the image.Given the increasing role of ethnic lobbying in the world politics, it is necessary to study the history,dynamics and current position of the Ukrainian Diaspora in the Republic of Kazakhstan regarding it as apowerful factor of political, economic, informational influence.In order to conduct the research several methods are to be used. They are: systems approach, historicalmethod and comparative analysis. Conclusions of the research can be used for predicting of tendenciesin the sphere of cultural and humanitarian cooperation between Ukraine and Kazakhstan.Key words: Ukrainians in the Republic of Kazakhstan; resettlement; national and cultural revival.